Genome-wide identification and comparative analysis of CLE family in rapeseed and its diploid progenitors - Xie, Meili; Zhao, Chuanji; Song, Min; Xiang, Yang; Tong, Chaobo (Frontiers in Plant Science, 2022)
Crop genomics and breeding CLAVATA3/EMBRYO SURROUNDING REGION-RELATED (CLE) proteins belong to a small peptide family in plants. During plant development, CLE gene family members play a pivotal role in regulating cell-to-cell communication and stem cell maintenance. However, the evolutionary process and functional importance of CLEs are unclear in Brassicaceae. In this study, a total of 70 BnCLEs were identified in Brassica napus (2n = 4x = 38, AnCn): 32 from the An subgenome, 36 from the Cn subgenome, and 2 from the unanchored subgenome. Meanwhile, 29 BrCLE and 32 BoCLE genes were explored in Brassica rapa (2n = 2x = 20, Ar) and Brassica oleracea (2n = 2x = 18, Co). Phylogenetic analysis revealed that 163 CLEs derived from three Brassica species and Arabidopsis thaliana can be divided into seven subfamilies. Homology and synteny analyses indicated whole-genome triplication (WGT) and segmental duplication may be the major contributors to the expansion of CLE family. In addition, RNA-seq and qPCR analysis indicated that 19 and 16 BnCLEs were more highly expressed in immature seeds and roots than in other tissues. Some CLE gene pairs exhibited different expression patterns in the same tissue, which indicated possible functional divergence. Furthermore, genetic variations and regional association mapping analysis indicated that 12 BnCLEs were potential genes for regulating important agronomic traits. This study provided valuable information to understand the molecular evolution and biological function of CLEs in B. napus and its diploid progenitors, which will be helpful for genetic improvement of high-yield breeding in B. napus.